Pemimpin Milenial dalam Mengembangkan Budaya Kerja Fleksibel Bagi Generasi Z di Industri Kreatif - Balqis Zulfatun Nabila; Pardiman Pardiman; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The rapid development of digital technology has significantly transformed work patterns across various sectors, including the creative industry. This sector relies heavily on innovation, creativity, and adaptability, making flexible work practices increasingly relevant, particularly for Generation Z, which now dominates the workforce. This study aims to analyze the role of millennial leaders in developing a flexible work culture for Generation Z in the creative industry. A qualitative approach with a phenomenological design was employed to explore leadership practices and employee perceptions in depth. The research was conducted at Kinaryo Studio and Blooms Organizer in Malang City. Data were collected through in-depth interviews, participant observation, and documentation involving millennial leaders and Generation Z employees. Data analysis was carried out through data condensation, data presentation, and conclusion drawing, supported by triangulation to ensure the validity of the findings. The results show that millennial leaders interpret flexible work culture as a results-oriented system that allows employees to manage their working time and location while maintaining responsibility for achieving organizational targets. Generation Z perceives flexibility as an essential factor that supports motivation, job satisfaction, and work–life balance. Leadership strategies such as open communication, trust-based management, and outcome-based performance evaluation contribute to stronger work engagement, employee loyalty, and improved productivity within the creative industry. Keywords : Millennial Leadership, Flexible Work Culture, Generation Z, Creative Industry.